The Development of a Mini-research-based Digital Module Using Sigil in Endocrinology Learning - Rahma Widiantie; Ina Setiawati; Anna Fitri Hindriana; Edi Junaedi; Elsa Chintya (Program Studi Pendidikan Biologi, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Kuningan, 2024)
Developing technology-based teaching materials that are more innovative, creative, effective, efficient and contextual is a demand in learning. Lecturers are required to be able to develop media and teaching materials by utilizing technological advances. The aim of this research is to develop complete teaching materials or modules consisting of materials, student worksheets, evaluations, assessment techniques and learning videos to improve students' mastery of concepts using the sigil application. The characteristics of the module developed is a digital module based on mini research, where mini research learning can improve students’, problem solving abilities and integrated science process skills. The method in this research is the Design and Development Research method with the PPE model which includes 3 stages: Planning, Production, and Evaluation. The results of the research are digital modules based on mini PPE research models, planning by analyzing the need to design flowcharts and story boards from digital modules, production by creating digital modules, namely compiling the module framework and endocrinology material in Microsoft Word software (html format) the file is opened in the software sigil editor is saved in epub format, evaluation by material experts and media experts by assessing the feasibility of the digital sigil module based on mini research in endocrinology learning. The results of the validity test based on the appropriate aspects of content, language and presentation are valid. The results of the practicality test by students on the aspects of content, language and usefulness are valid. Mini-research-based digital modules using sigil software are valid, practical and suitable for use in Endocrinology courses with the advantage of facilitating thinking skills and increasing student learning independence.